Assistência a saúde das pessoas com doença falciforme na região do Recôncavo baiano, Brasil - Oliveira, Roberto Ferreira de (2012)
Sickle cell disease (SCD) is considered a public health problem by its transcendence, in view of early mortality and cause all kinds of human suffering. Despite being an incurable disease has been shown that comprehensive care with prophylactic measures and monitoring indicators have decreased morbidity and mortality caused by DF. One of the actions to face this disease is neonatal screening (Guthrie test). This will enable children to be diagnosed early and thus complications are minimized This study estimated the incidence of stroke and sickle cell disease and coverage of neonatal screening in the city of Cachoeira in the period from 2006 to 2010. It also analyzed the nurses' knowledge of the Family Health Program of nine municipalities in the region of Bahia recôncavo. The State Newborn Screening Program constituted a source of data and also used a questionnaire which was formulated from the policy line of the Ministry of Health to assess the knowledge of health professionals about the disease. In the period from 2006 to 2010, 2205 children were born in the city of Cachoeira and 1836 were screened representing a coverage of 83.2%%. The incidence of sickle cell trait and disease in the neonatal population undergoing the test was estimated at 6.7% and 0.71% respectively 61 nurses participated in the research of the nine municipalities surveyed. The results revealed that the field epidemiology of the disease, the eight questions, 81.2% knew an average of 6.5 questions. Already in the field clinical manifestations of sickle cell disease consists of 13 questions, 54.4% of participants agreed on average 7.2 questions and finally the field management of the child with the condition mentioned above, consists of 26 questions, hit 74.3% on average 17.1. 50.7% of (the) participants had a below average performance. We conclude that the coverage of the program reached the minimum target required by the health ministry. The incidences are high when compared to other studies and is necessary investments in the training of nurses in primary care to improve quality of life and prevent premature mortality among people with sickle cell disease.